2012
DOI: 10.1177/1010539512440818
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Educational Stress Scale for Adolescents (ESSA) in Vietnam

Abstract: The ESSA is a suitable measure for school-based mental health research in Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…In the current study, the CES-D had very good reliability similar to that reported for the original version [ 12 ] and reasonably similar to studies employing this scale in adolescents and young adults without HIV in Vietnam, where Cronbach’s alpha has been reported to range from 0.78 to 0.86 [ 25 , 26 , 29 , 43 ]. Compared to other validation studies, especially in non-US, high HIV burden settings, the Cronbach’s alpha in this study was similar to a self-report-based study in tuberculosis and HIV patients in Zambia (α = 0.84) [ 15 ] but lower than an interview-based study among pregnant women with and without HIV in Uganda (α = 0.92) [ 16 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the current study, the CES-D had very good reliability similar to that reported for the original version [ 12 ] and reasonably similar to studies employing this scale in adolescents and young adults without HIV in Vietnam, where Cronbach’s alpha has been reported to range from 0.78 to 0.86 [ 25 , 26 , 29 , 43 ]. Compared to other validation studies, especially in non-US, high HIV burden settings, the Cronbach’s alpha in this study was similar to a self-report-based study in tuberculosis and HIV patients in Zambia (α = 0.84) [ 15 ] but lower than an interview-based study among pregnant women with and without HIV in Uganda (α = 0.92) [ 16 ].…”
Section: Discussionsupporting
confidence: 84%
“…Factor analysis conducted with samples of general population and psychiatric patients indicates that the CES-D has four factors: depressed affect, positive affect, somatic complaints and interpersonal problems [ 12 ]. Although the CES-D was available in the Vietnamese language in previous studies [ 23 , 24 , 29 ], the original version was also translated into Vietnamese independently both by the first author and an accredited translator. Differences between researcher and the accredited translator were discussed.…”
Section: Methodsmentioning
confidence: 99%
“…There may be a number of contributing factors. Although no associations were found between self-reported (single item) ‘academic achievement’ and any of the three risk behaviors, media reports and other research in Vietnam (26, 27) have highlighted educational stress to be a significant problem in Vietnam. Pressure to succeed academically has negative effects on the well-being and behavior of young people, especially children living in urban areas (18, 19, 21, 26).…”
Section: Discussionmentioning
confidence: 64%
“…Educational stress was measured by the Vietnamese version of the Educational Stress Scale for Adolescents (ESSA-VN) [ 15 ]. Responses to the 16 items are on a 5-point Likert-type scale ranging from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%